Study on the effects of led light on physiological and morphological characteristics of dang shen (Codonopsis sp.) growth in in vitro condition - Hung, Nguyen Khac; Ngoc, Pham Bich; Thu Hien, Nguyen Thi; Thuy Huong, Nguyen Thi; Gam, Do Thi; Hung, Le Duy; Ha, Chu Hoang (Academia Journal of Biology, 2016)
Codonopsis sp. has been widely used in Vietnam‘s folk medicine for years due to its marvelous characteristics, such as health enhancing, immune promoting etc., Dang shen is naturally being everexploited that could lead it to extinction. LED technology has been applied in micro propagation with various advantages, such as long life, convenient size, easy automated, electric saver and eco-friendly. This research aims to evaluate the effects of distinguished LED categories on the development of Dang shen and to assess the applicable ability of LED in this plant in vitro cultivated. The results indicated that different light conditions have manifold effects on plant morphology and physiology. While single wavelength 450 nm (Blue light) and 660 nm (Red light) caused the abnormal development of plant, the combined wavelength type BR (80% Red light: 20% Blue light) resulted in extremely promoting plant growth ability. There was approximate 90% of shoot induced roots after 30 days period cultured under BR LED, in contrast, only 75% in control light condition. Furthermore, the numbers of roots emerged, the roots length and the plant height under BR light conditions were all improved, comparing with other investigated conditions. Our significant outcomes certainly contributed a solution in which LED light, especial combined type (80% red light: 20% blue light) could replace fluorescent in plant cell culture.